Identification of differences between group and individual life insurance for employees - Anna Maria Piechota (Economic and Environmental Studies (E&ES), 2019)
Group life insurance for employees is one of numerous voluntary insurance products covering employees' personal risks. It can be an important complement to mandatory insurance arrangements (especially social insurance schemes) that provide personal coverage for workers. While employees may take out their life insurance on an individual basis, employer-offered group life insurance is an attractive alternative. Joining a group insurance plan is an employee's individual decision that should be taken based on his or her knowledge of the terms of coverage. The purpose of this article is to point out the differences between employee group life coverage and individual life insurance, with a particular emphasis on insurance funding aspects and how they affect certain aspects of relevance to employees.
Keywords: G22; 330; group life insurance; life insurance; personal risks